Homeroom Teachers' Perspectives on Identifying Factors Contributing to Students' Learning Difficulties at MTs Pembangunan Mandirancan - Salsabila Aisya Untari; Elin Maulida Rahmawati; Andi Kiswanto (Ma'soem University, 2026)
Learning difficulties remain one of the major challenges affecting students' academic achievement and overall development. Identifying the factors contributing to these difficulties is essential for designing appropriate educational support and intervention strategies. This study aimed to explore homeroom teachers' perspectives on the factors contributing to students' learning difficulties at MTs Pembangunan Mandirancan. A qualitative descriptive approach was employed. Data were collected through classroom observations and semi-structured interviews with the homeroom teacher of Grade VIII-A as the primary informant. The collected data were analyzed using the interactive model of data analysis, including data reduction, data display, and conclusion drawing. The findings revealed that students' learning difficulties were primarily characterized by low learning motivation, difficulties in understanding subject matter, poor concentration during classroom activities, and ineffective learning habits. These difficulties were influenced by both internal factors, including motivation, self-confidence, learning readiness, and academic ability, and external factors such as family support, peer influence, excessive use of digital devices, and study habits. The study emphasizes the importance of collaborative efforts among homeroom teachers, subject teachers, school counselors, parents, and school administrators in identifying and addressing students' learning difficulties through comprehensive guidance and educational support.